Pengaruh Burnout terhadap Kecerdasan Emosional, Self-Efficacy, dan Kinerja Dokter Muda di Rumah Sakit Dr. Soebandi - Raden Roro Lidia Imaniar; R. Andi Sularso (Universitas Proklamasi 45 Yogyakarta, 2016)
The Effect Of Burnout On Emotional Intelligence, Self-Efficacy, And Co-Assistant Performance In dr. Soebandi Hospital Jember.The purpose of the studi was to examine and explain (1) the effect of burnout on co-assistant performance; (2) the effect of burnout on emotional intelligence; (3) the effect of burnout on self-efficacy; (4) the effect of emotional intelligence on co-assistant performance; and (5) the effect of selfefficacy on co-assistant performance.The sampel of this study consisted of 94 coassistant in dr. Soebandi Hospital Jember. Sample was chosen based on porpusive random sampling technique. Questionnaire was the main instrument to collect data. Data was analyzed using descriptive analyses employing Partial Least Square (PLS).The findings in this study is (1) burnout has a significant and negative effect coassistant performance; (2) burnout has a significant and positive effect on emotional intelligence; (3) burnout has a non-significant and positive effect on self-efficacy; (4) emotional intelligence has a significant and positive effect on co-assistant performance; and (5) self-efficacy has a significant and positive effect on co-assistant performance.